Non-syndromic Keratocystic Odontogenic Tumor Involving the Maxillary Sinus: Case Report - Rabelo, Gustavo Davi; Henriques, João Cesar Guimarães; Macedo, José Humberto; Silva, Claudia Jordão; Cardoso, Sergio Vitorino; Loyola, Adriano Mota; Durighetto, Antônio Francisco, Junior (Arquivos Internacionais de Otorrinolaringologia, 2010)
Introduction: The odontogenic keratocyst tumor is rarely found in maxilla.Case Report: This article describes a report of a case of a 60-year-old Caucasian female with an asymptomatic growth in the region of the posterior maxilla tumor diagnosed as odontogenic keratocyst. We discuss the diagnosis and workup for this type of injury.
Keywords: odontogenic tumors; maxillary sinus; radiology; surgery